A Comparative Study of Conventional Aerator and Microbubble Generator in Aerobic Reactors for Wastewater Treatment - Marbelia, L. (Institute of Physics Publishing, 2020)
Aeration in aerobic reactor for wastewater treatment has an important role in determining its performance. In this case, sufficient oxygen supply with good mixing is necessary to guarantee a good pollutant biodegradation. However, biodegradation is not the only parameter to consider when designing an aerator, energy consumption and cost also have important roles. In this study, a conventional air diffuser (CAD) and a low-cost microbubble generator (MBG) were compared in a 400-L reactor for two aerobic wastewater treatment process configurations, i.e. suspended culture and attached culture (with pumice stones). Dissolved oxygen (DO) concentration throughout the reactor was initially investigated with tap water. Results indicated that the maximum DO which could be obtained for the two type of aerators were almost similar, in the range of 7.7 to 7.9 mg/L. But the lowest values are different, i.e. 5.6 mg/L for CAD and 6.8 mg/L for MBG, showing that homogeneity was better for MBG. This might be due to smaller bubble sizes produced by MBG which were able to stay inside the liquid for a longer time. Afterward, comparison of the two aerators were performed for aerating activated aerobic sludge. Without pumice stones, DO concentration for MBG and CAD was almost similar, but for MBG, lower values were found in the bottom of the tank indicating the higher activated sludge concentration. When using pumice stones, MBG again shows its superiority indicated by a higher DO values reaching 6.4 mg/L, compared to 5.6 mg/L for the CAD. These results revealed the promising potential of MBG as a low-cost aerator to be used in aerobic reactor for wastewater treatment with attached culture. Â© 2020 IOP Publishing Ltd.